2004
DOI: 10.1038/sj.cdd.4401428
|View full text |Cite
|
Sign up to set email alerts
|

p53-Independent ceramide formation in human glioma cells during γ-radiation-induced apoptosis

Abstract: Although the p53 tumor-suppressor gene product plays a critical role in apoptotic cell death induced by DNA-damaging chemotherapeutic agents, human glioma cells with functional p53 were more resistant to c-radiation than those with mutant p53. U-87 MG cells with wild-type p53 were resistant to c-radiation. U87-W E6 cells that lost functional p53, by the expression of type 16 human papillomavirus E6 oncoprotein, became susceptible to radiation-induced apoptosis. The formation of ceramide by acid sphingomyelinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
83
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 40 publications
10
83
0
Order By: Relevance
“…Although our data are in agreement with previous findings using B13 (Selzner et al, 2001;Ogretmen and Hannun, 2004) or NOE (Hara et al, 2004) to block CDases, it has been reported that primary human SV-40 transformed skin fibroblasts or lymphocytes from Farber disease patients, a genetic disorder characterized by a decrease in acid CDase, were as sensitive to DNRinduced cell death as cells from healthy controls (Burek et al, 2001). This reported discrepancy with our findings might well be owing to the tumor specificity or type of cells used.…”
Section: Discussionsupporting
confidence: 94%
“…Although our data are in agreement with previous findings using B13 (Selzner et al, 2001;Ogretmen and Hannun, 2004) or NOE (Hara et al, 2004) to block CDases, it has been reported that primary human SV-40 transformed skin fibroblasts or lymphocytes from Farber disease patients, a genetic disorder characterized by a decrease in acid CDase, were as sensitive to DNRinduced cell death as cells from healthy controls (Burek et al, 2001). This reported discrepancy with our findings might well be owing to the tumor specificity or type of cells used.…”
Section: Discussionsupporting
confidence: 94%
“…Although speculative, our results also tend to suggest that nSMase3 may not be responsible for lengthened periods of ceramide production that occur in hours to days following treatment with g-radiation or Adriamycin (11,13,25). The possibility therefore exists that one of several other ceramidegenerating pathways may be responsible for the extended production of ceramide.…”
Section: Discussionmentioning
confidence: 65%
“…To the best of our knowledge, this is the first report of p53 modulating the expression of an individual nSMase; however, the notion that p53 facilitates decreased ceramide levels is not without precedence. For instance, Hara et al (25) have reported that g-radiation causes a p53-dependent increase in acid ceramidase, an enzyme that hydrolyzes proapoptotic ceramide to form growth-promoting sphingosine. Reciprocally, previous studies have shown the p53-dependent increases in ceramide levels via down-regulation of sphingosine-kinase-1, thus forming the concept that p53 promotes ceramide generation rather than promoting its breakdown or abrogating its synthesis (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We established the p53 knock-down (HepG2-p53-KD) and the control (HepG2-p53-Cont) cell lines as described previously (Hara et al 2004), which were derived from a hepatoblastoma cell line (HepG2 that contains wild-type p53). In brief, HepG2 cells were infected with SI-MSCV-puro-H1R-p53Ri retrovirus for down-regulation of p53 expression and with SI-MSCV-puro-H1R retrovirus for negative control.…”
Section: Rna Interferencementioning
confidence: 99%